IMPROVING THE EFFICIENCY OF POWER TRANSMISSION USING A RECTIFIER CONVERTERS WITH VARIABLE STRUCTURE POWER CIRCUIT - Basov, H. H.; Falaleiev, M. I. (Science and Transport Progress, 2007)
Different ways of increasing efficiency of electric transmission in the rolling stock and methods of improving the power efficiency in the use of valve transformers with the variable structure of power circuit are examined in the article. The methods of designing electric transmissions with variable structure of power circuits have been offered.